Investigating student of Primary School Teachers views on science and education in Indonesia - A K Jayadinata; K A Hakam; A Munandar (Pascasarjana Universitas Pendidikan Indonesia, 2020)
Environmental changes due to the irresponsible application of technological innovation and human behavior that are not environmentally friendly have caused various environmental crises. Various studies recommend the importance of the role of science education in building citizens scientific literacy abilities. Therefore, this ability needs to be possessed by all students of primary school teachers (PGSD students) as part of citizens. PGSD students literacy scientific abilities are focused on the nature of science (NOS) and attitudes toward teaching NOS. This study aims to obtain information about the views of students about the nature of science concept (NOS) and attitudes toward teaching NOS obtained from filling questionnaire instruments views on science and education (VOSE). Data were obtained from 132 students of the 2017/2018 academic year who attended the lecture (GD302) in science education in elementary schools. The findings of this study revealed that PGSD students were able to feel some of the problems of cencept NOS and held a positive attitude towards some NOS teaching problems.